Ankle-brachial index and diabetic neuropathy: study of 225 patients - Liliana Chevtchouk; Marcio Heitor Stelmo da Silva; Osvaldo José Moreira do Nascimento (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To evaluate neuropathic pain and peripheral vascular disease in diabetics and compare this with the length of time since diagnosis in type 1, and type 2 diabetes. Methods A cross-sectional study with 225 diabetics chosen from their responses on the DN4 questionnaire, who were then evaluated with the ankle-brachial index (ABI), separating type 1 diabetes from type 2 diabetes. Results A higher incidence of neuropathic pain in those over 60 years of age showed an ABI > 1.3. Neuropathic pain was related to an abnormal ABI in 144 patients (64.2%). A statistically significant value was obtained in type 2 diabetes patients with more than 10 years from disease onset, 69 with altered ABI and 25 with normal ABI. There was an altered ABI (< 0.9) observed in 33% of type 1 diabetes patients and in 67% of type 2 diabetes patients. Conclusion The ABI test in type 1 diabetes and type 2 diabetes patients is important even in those who are asymptomatic. A diagnosis of more than 10 years prior, regardless of the presence of neuropathic pain or ischemic signs, altered the ABI.